Constitution of India - Shree ram law house; Bare Act (Chandigarh Shree Ram Law House, 2024)
The Constitution of India as amended by the constitution (One hundred and fifth amendment) act, 2021. The Jammu and Kashmir reorganisation act, 2019.
Keywords: Constitution of India